Tabagismo materno durante a gestação e medidas antropométricas do recém-nascido: um estudo de base populacional no extremo sul do Brasil Maternal smoking during pregnancy and anthropometric measurements of newborns: a population-based study in southern of Brazil - Linjie Zhang; David A. González-Chica; Juraci A. Cesar; Raúl A. Mendoza-Sassi; Betina Beskow; Natália Larentis; Tatiana Blosfeld (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
Este estudo transversal de base populacional teve por objetivo investigar a prevalência de tabagismo materno durante a gestação e seu impacto sobre as medidas antropométricas do recém-nascido. Aplicou-se questionário padronizado a todas as parturientes nas maternidades do Município de Rio Grande, Rio Grande do Sul, Brasil, em 2007. Foram obtidas medidas de peso, comprimento e perímetros cefálico dos recém-nascidos. A prevalência do tabagismo materno na gestação foi de 23%, enquanto a prevalência da exposição passiva ao fumo foi de 29%. Após ajuste para possíveis fatores de confusão, comparados aos recém-nascidos de mães que nunca fumaram, aqueles nascidos de mães fumantes durante toda a gestação tiveram ao nascer, em média, redução de 223,4g (IC95%: 156,7; 290,0) no peso, de 0,94cm (IC95%: 0,60; 1,28) no comprimento e de 0,69cm (IC95%: 0,42; 0,95) no perímetro cefálico. Concluiu-se que a prevalência de tabagismo materno na gestação é alta no Município de Rio Grande. Tabagismo materno durante toda a gestação teve impacto negativo nas medidas antropométricas do recém-nascido. This cross-sectional study aimed to investigate the prevalence of maternal smoking during pregnancy and its impact on anthropometric measurements of newborns. A standardized questionnaire was applied to all pregnant women admitted for delivery in the maternity units in Rio Grande, Rio Grande do Sul State, Brazil, in 2007. Measurements were taken of the newborns' weight, length, and head circumference. Prevalence rates were 23% for maternal smoking during pregnancy and 29% for exposure to environmental tobacco smoke. After adjusting for potential confounding factors, compared with those whose mothers never smoked, newborns whose mothers smoked throughout pregnancy showed average decreases of 223.4 g in birth weight (95%CI: 156.7;290.0), 0.94 cm in birth length (95%CI: 0.60;1.28), and 0.69 cm in head circumference (95%CI: 0.42-0.95). In conclusion, prevalence of maternal smoking during pregnancy was high in this municipality. Maternal smoking during pregnancy was inversely associated with birth weight, length, and head circumference.